2015
DOI: 10.1016/j.amepre.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating Traditional Healing Into Preventive Medicine Residency Curriculum

Abstract: Comprehensive cultural competency includes knowledge and awareness of culturally based healing and wellness practices. Healthcare providers should be aware of the individual patient's beliefs, culture, and use of culturally based health practices because patients may adopt such practices for general wellness or as adjunct therapies without the benefit of discussion with their healthcare provider. This article describes the culturally based traditional healing curriculum that has been implemented in the Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The integration of traditional medicine into existing medical education environments was showcased through a residency training program as described by Kessler et al [ 70 ]. In 2011, the University of New Mexico Public Health department and their General Preventive Medicine Residency Program in the United States started to integrate traditional healing into the resident training curriculum with full implementation completed by 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of traditional medicine into existing medical education environments was showcased through a residency training program as described by Kessler et al [ 70 ]. In 2011, the University of New Mexico Public Health department and their General Preventive Medicine Residency Program in the United States started to integrate traditional healing into the resident training curriculum with full implementation completed by 2015.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, the University of New Mexico Public Health department and their General Preventive Medicine Residency Program in the United States started to integrate traditional healing into the resident training curriculum with full implementation completed by 2015. An innovative approach was used in the teaching delivery by utilizing a compendium of training methods, which included learning directly from traditional healers and direct participation in healing practices by residents [ 70 ]. The “incorporation of this residency curriculum resulted in a means to produce physicians well trained in approaching patient care and population health with knowledge of culturally based health practices in order to facilitate healthy patients and communities” [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…This situation is gradually changing, as some medical and nursing schools have become increasingly informed about safe, culturally congruent, and evidence-based alternative, complementary, and integrative approaches to health care delivery. 3,4,5,6,7,8,9,10 Patient challenges. TM/H is critical to the identity and culture of tribal nations and the ways that they relate to the world around them.…”
Section: Practice Challengesmentioning
confidence: 99%
“…Currently, many companies produce various types of medicines with varying prices and different brand. There was study revealed that the healing of the disease could use various types of medicines for the patients [12]. Thus, the price of medicines is challenging to control.…”
Section: ) Medicine Inventory For the Elderlymentioning
confidence: 99%